Splicing predictions, minigene analyses, and ACMG-AMP clinical classification of 42 germline PALB2 splice-site variants - Valenzuela Palomo, Alberto; Bueno Martínez, Elena; Sanoguera Miralles, Lara; Lorca, Víctor; Fraile Bethencourt, Eugenia; Esteban Sánchez, Ada; Gómez Barrero, Susana; Carvalho, Sara; Allen, Jamie; García Álvarez, Alicia; Pérez Segura, Pedro; Dorling, Leila; et al. (My University, 2021)
PALB2 loss-of-function variants confer high risk of developing breast cancer. Here we present a systematic functional analysis of PALB2 splice-site variants detected in approximately 113,000 women in the large-scale sequencing project Breast Cancer After Diagnostic Gene Sequencing (BRIDGES; https://bridges-research.eu/). Eighty-two PALB2 variants at the intron-exon boundaries were analyzed with MaxEntScan. Forty-two variants were selected for the subsequent splicing functional assays. For this purpose, three splicing reporter minigenes comprising exons 1¿12 were constructed. The 42 potential spliceogenic variants were introduced into the minigenes by site directed mutagenesis and assayed in MCF-7/MDA-MB-231 cells. Splicing anomalies were observed in 35 variants, 23 of which showed no traces or minimal amounts of the expected full-length transcripts of each minigene. More than 30 different variant-induced transcripts were characterized, 23 of which were predicted to truncate the PALB2 protein. The pathogenicity of all variants was interpreted according to an in-house adaptation of the American College of Medical Genetics and Genomics and the Association for Molecular Pathology (ACMG-AMP) variant clas sification scheme. Up to 23 variants were classified as pathogenic/likely pathogenic. Remarkably, three 1,2 variants (c.49-2A>T, c.108+2T>C, and c.211+1G>A) were classified as variants of unknown significance, as they produced significant amounts of either in-frame transcripts of unknown impact on the PALB2 protein function or the minigene full-length transcripts. In conclusion, we have significantly contributed to the ongoing effort of identifying spliceo genic variants in the clinically relevant PALB2 cancer susceptibility gene. Moreover, we suggest some approaches to classify the findings in accordance with the ACMG-AMP rationale. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd on behalf of The Pathological Society of Great Britain and Ireland. Keywords: breast cancer; susceptibility genes; PALB2; splicing; aberrant splicing; VUS; functional assay; minigene; clinical interpretation